KNOWLEDGE MANAGEMENT TECHNOLOGY USING SECI AND WIL TO IMPROVE PERFORMANCE OF IN-FORMATION TECHNOLOGY DIVISION IN PANGESTU JAYA LTD. - Joang Ipmawati; Yana Hendriana (Universitas Mulia, 2021)
Information Technology Division is one of the divisions in Pangestu Jaya Ltd. which engaged in IT Department, where in this division there are several sub-divisions that are interrelated and have the duty and responsibility of each individual to improve services in The company. Turnover is one of the major obstacles in order to still be able to keep the knowledge technology in the company, because there are still many employees with outsourced status who often do turnover in IT division, so difficult to keep the knowledge. therefor need a knowledge management technology which is capable of storing, distributing knowledge in order to renew even while maintaining corporate knowledge. The system design of this research used SECI and WIL (Work Integrated Learning).